The effect of increased intensity training on developing endurance for velocity and shooting accuracy from vaulting in young basketball players - Abdulaaima Kadhim Alsaedi, Mazin; Ahmed Neamah, Shihab; Kadhim Ashour, Mohammed (International Journal of Psychosocial Rehabilitation, 2020)
The pursuit of higher levels of sport and breaking records for the types of sporting activities and events that are captured in general and basketball in particular is an important topic that enjoys the interest of workers in the sports field, and as a result of this pursuit, many modern activities have been discovered, as well as scientific theories in the field of sports training that have led to explaining many phenomena and helped in finding the best solutions to many problems and topics aimed at improving the technical and digital performance of various sports competitions. As for the research problem, physical training is an important means and one of the very necessary requirements in monitoring the development of the functional and physical level reached by the player or team and through what the researchers touched and their proximity to it. The youth association and their knowledge of many researches and studies found the necessity to prepare increased manual training. The intensity of the use of devices and auxiliary devices to develop the functional and physical condition of young basketball players, where the research problem lies in that previous special exercises using devices and tools did not take into account that every skill performance depends mainly on the physical side and the functional side, as the archery skill cannot be performed from jumping If it is not accompanied by physical or motor ability, the shooting jump consists of the scoring skill and the explosive power of the legs and arms as well as the endurance, and the case applies to the rest of the skills. The study aimed to investigate the effect of increasingly intense physical training on developing the endurance of speed for young basketball players and improving the accuracy of shooting from jumping. Research Hypotheses: There are statistically significant differences between the results of the pre- and post-tests in the development of the shooting accuracy variable among young basketball players. Research methodology: The researchers used the experimental approach with the design of one experimental group and the pre- and post-tests for their suitability and the nature of the problem to be solved. The researchers found that the variables obtained from the FATMET BROO device were a real indicator of the development of the functional variables (VE - RF - VO2max)). Great importance is given to the career readiness of the players and the physical effort required of young basketball players.